2009
DOI: 10.1002/bmc.1179
|View full text |Cite
|
Sign up to set email alerts
|

Histidine affinity chromatography of homo‐oligonucleotides. Role of multiple interactions on retention

Abstract: The recent application of histidine-agarose affinity supports in plasmid purification takes advantage of the biorecognition of nucleic acid bases by the histidine ligand. This consideration prompted the need for better understanding the interactions involved in affinity chromatography of plasmid DNA with the histidine-agarose support. In this work, we used synthetic homo-deoxyoligonucleotides with different sizes (1-30 nucleotides long), to explore the effect of several conditions like hydrophobic character of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
8
30
0
Order By: Relevance
“…The elution profiles obtained when loading an oligonucleotide sample (e. g. monoA or polyA30) onto the arginine-agarose column have shown that oligonucleotide retention increased when the temperature was increased (Table 1). This is the reverse mechanism previously found for histidine-AC of homo-oligonucleotides, where the interaction was mainly attributed to base exposition [24]. This work is in agreement with previous studies, where it was described that the temperature increase directly influenced the retention of the pDNA to the arginine stationary phase, being verified an increased retention [9].…”
Section: Temperaturesupporting
confidence: 91%
See 2 more Smart Citations
“…The elution profiles obtained when loading an oligonucleotide sample (e. g. monoA or polyA30) onto the arginine-agarose column have shown that oligonucleotide retention increased when the temperature was increased (Table 1). This is the reverse mechanism previously found for histidine-AC of homo-oligonucleotides, where the interaction was mainly attributed to base exposition [24]. This work is in agreement with previous studies, where it was described that the temperature increase directly influenced the retention of the pDNA to the arginine stationary phase, being verified an increased retention [9].…”
Section: Temperaturesupporting
confidence: 91%
“…This behaviour suggests that different secondary structures of the oligonucleotide can coexist under these conditions. These secondary structures were already described as frequent and are usually designated by guanine quadruplexes that may occur due to the possible interactions between molecules of guanine leading to inter-or intramolecular associations, depending on the size of oligonucleotide [23,24]. The quadruplexes can form arrays of four hydrogen bonds in which each base acts as both donor and acceptor of two hydrogen bonds with other guanines, and pairing between bases is of Hoogsteen type [25].…”
Section: Oligonucleotide Molecular Massmentioning
confidence: 97%
See 1 more Smart Citation
“…A fundamental study performed with synthetic oligonucleotides showed that the presence of secondary structures on polyA and polyG oligonucleotides has a significant influence on retention, similar to what is obtained with plasmids. In this study, it was also verified that His interacts preferentially with the guanine and adenine bases (Sousa et al, 2009b), as described at atomic level (Luscombe et al, 2001;Hoffman et al, 2004). The similar studies performed using Arg (Sousa et al, 2008b) and Lys (Sousa et al, 2009a) chromatography to purify pDNA, also proved the presence of a specific interaction with plasmid molecules, and a particular recognition of sc isoform.…”
Section: Amino Acid-nucleic Acids Interaction In Affinity Chromatographysupporting
confidence: 79%
“…A fundamental additional study performed with synthetic oligonucleotides to explain the retention mechanism in the histidinesupport, also corroborates this hypothesis since the presence of secondary structures on polyA and polyG oligonucleotides has a significant influence on retention (Sousa et al 2009a). In addition, it was verified that histidine interacts preferentially with the guanine base (Sousa et al 2009a). Figure 2 represents the specific recognition of guanine by the histidine support, by performing two hydrogen bonds.…”
Section: Affinity Chromatographysupporting
confidence: 60%